Business durability: concept, research, findings - Rivera Rodríguez, Hugo Alberto (Cuadernos de Administración, 2012)
The business management literature during the last 20 years has studied different aspects of corporate sustainability, mainly the related with the leader's role; the association with profitability, and the effects that it generates on the business.However, there are many aspects which should be deepened. The first of them is to solve wide terminological diversity. When not having consent on the concept, they are used of way indiscriminate terms like longevity, sustainability, success, survival, duration, enduring etc., which instead of clarifying, they generate confusion. On the other hand, neither there is enough evidence to suggest alternative that allow to the companies to be able to be lasting. The article that is presented is based in an exhaustive revision of the concept of managerial sustainability, and includes a list of the main findings found in the literature on the conditions that can facilitate the business sustainability. With it is sought it of advancing in the study of the relationship between sustainability, the strategic behavior of the companies and financial performance